Evaluation of technologies approved for supplemental payments in the United States. (17th June 2019) - Judson, Timothy J; Dhruva, Sanket S; Redberg, Rita F
Abstract : Supplemental payment programmes can increase access to new technologies, but Timothy Judson and colleagues find that some payments are made without clear evidence of safety and effectiveness